(untitled) (Journal of Civil Engineering Researchers, 2022)
Today, the use of nanoscale additives in the concrete industry with the aim of reducing the negative effects of Portland cement and improving the mechanical properties of concrete has received much attention. Also, in order to reduce the harmful environmental effects and increase the mechanical properties and durability of concrete, particles with high pozzolanic properties are used as a suitable alternative to ordinary cement in concrete. In this regard, geopolymer concrete using materials containing aluminosilicate materials with adhesive properties and filler, as an alternative to cement, has attracted the attention of researchers. Concrete resistance to high heat is of particular importance. Geopolymer concrete has a good performance against heat due to its strong structure. In the current study, slag-based geopolymer concrete was used with 0-2% polyolefin fibers and 0-8% nano-silica to improve its structure. After curing the specimens under dry conditions at a temperature of 60°C in an oven, they were subjected to Compressive strength, Tensile strength, and Drop weight hammer tests to evaluate their mechanical properties. all tests were performed at 90 days of age under ambient temperature (20 ℃) and high temperature (500 ℃). The addition of nano-silica enhanced the whole properties of the slag-based geopolymer concrete. Addition of up to 8% nanosilica to the geopolymer concrete composition at 20% temperature improved the compressive strength test results up to 21.94%, tensile strength up to 15.19% and impact energy up to 36.36%. Addition of up to 2% of polyolefin fibers to the geopolymer concrete composition improved the tensile strength up to 11.76%, the impact energy up to 8.26 times and the compressive strength drop up to 22.49%. Applying high heat to geopolymer concrete samples reduced the compressive strength up to 16%, tensile strength up to 21% and impact energy up to 72.72%. The effect of heat on the drop in results in control concrete is more than geopolymer concrete. In the following, by conducting the SEM test, a microstructure investigation was carried out on the concrete samples. In addition to their overlapping with each other, the results indicate the geopolymer concrete superiority over the regular concrete. Besides, it demonstrated the positive influence of nano-silica addition on the concert microstructure.